2017
DOI: 10.1016/j.ultsonch.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted mineralization of organic contaminants using a recyclable LaFeO3 and Fe3+/persulfate Fenton-like system

Abstract: A recyclable heterogeneous catalyst has been successfully developed for application in a Fenton-type advanced oxidation process without adding external HO. LaFeO was prepared from Fe(NO)·9HO and La(NO)·6HO by a simple sol-gel method and its catalytic efficiency was evaluated for mineralization of 4-chlorophenol using a Fenton-like process. The mineralization process was carried out under ultrasonication in presence of heterogeneous LaFeO catalyst with HO that was produced during ultrasonication. The mineraliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Feng et al reported that LFO showed 88% degradation efficiency in the third cycle while Babu et al reported that 90% efficiency of LFO was conserved after the fourth cycle. 53,54 Consequently, this study shows that the incorporation of graphene provides an increase in the stability and efficiency of LFO.…”
Section: Reusability Of Glfomentioning
confidence: 63%
“…Feng et al reported that LFO showed 88% degradation efficiency in the third cycle while Babu et al reported that 90% efficiency of LFO was conserved after the fourth cycle. 53,54 Consequently, this study shows that the incorporation of graphene provides an increase in the stability and efficiency of LFO.…”
Section: Reusability Of Glfomentioning
confidence: 63%
“…According to Figure 4, the removal efficiency attained by CFO was the higher than that of UV irradiation and PS, which are mainly due to the high oxidation capacity. However, this finding indicates that the oxidation of dye by these processes is rather limited [30,40]. The highest removal efficiency of dye by AC, compared to that of oxidation processes, can be due to high specific surface area.…”
Section: Catalytic Activity Of Dye In the Presence Of Ac/cfomentioning
confidence: 89%
“…Similar sleep‐Fenton systems have been developed for the degradation of sodium cefazolin, paracetamol, 4‐chlorophenol, IBU, metronidazole, and levofloxacin by different researchers 50, 116–120. In all systems, there was a maximum degradation with the hybrid sleep‐Fenton process.…”
Section: Synergistic Effects Of Ultrasound Associated With Other Degradation Technologiesmentioning
confidence: 99%